The bottomonium spectrum at finite temperature from N f = 2 + 1 lattice QCD - Chris Allton (Journal of High Energy Physics, 2014)
We present results on the bottomonium spectrum at temperatures above and below the deconfinement crossover temperature, Tc, from dynamical lattice QCD simulations. The heavy quark is treated with a non-relativistic effective field theory on the lattice and serves as a probe of the hot medium. Ensembles with a finer spatial lattice spacing and a greater range of temperatures below Tc than those previously employed by this collaboration are used. In addition, there are Nf=2+1 flavours of Wilson clover quark in the sea with Mπ≈400 MeV and we perform a more careful tuning of the bottom quark mass in this work. We calculate the spectral functions of S and P wave bottomonium states using the maximum entropy method and confirm earlier findings on the survival of the ground state S wave states up to at least 2Tc and the immediate dissociation of the P wave states above Tc.